PENGEMBANGAN MEDIA PEMBELAJARAN ENVIRONBYTIKTOK DENGAN SOSIO-SCIENTIFIC ISSUES ALIH FUNGSI HUTAN IBU KOTA NUSANTARA UNTUK MENDUKUNG LITERASI LINGKUNGAN SISWA SMA(THE DEVELOPMENT OF ENVIRONBYTIKTOK (LEARNING MEDIA ADDRESSING SOCIO-SCIENTIFIC ISSUES ON THE LAND USE CONVERSION OF THE NUSANTARA CAPITAL CITY FORESTS TO ENHANCE HIGH SCHOOL STUDENTS ENVIRONMENTAL LITERACY) - Putra, Desta Tri Anggara; Suhartini, Suhartini (Jurnal Edukasi Biologi, 2025)
The limitations of conventional learning media in improving the environmental literacy of high school students are a challenge in the digital era. To overcome this, media innovations, such as TikTok, are needed that are contextual and relevant to the habits of the younger generation. This study aims to determine the feasibility, practicality, readability, and effectiveness of TikTok-based biology learning media products with socio-scientific forest conversion issues in the Indonesian Capital City to support the environmental literacy of high school students. This research is a development research or Research and Development (R&D) with a 4D model (Define, Design, Development, Disseminate). The research subjects comprised material experts, media experts, biology teachers, and 36 SMA N 1 Godean students. The research instruments used were expert validation questionnaires, teacher assessment questionnaires, and student assessment questionnaires analyzed using qualitative and quantitative descriptive data analysis techniques, as well as pre-test and post-test assessments of students with N-Gain analysis. The results of the study showed that TikTok-based learning media with socio-scientific issues of forest conversion in the Indonesian Capital City to support environmental literacy of high school students was successfully developed in the form of EnvironByTikTok media. The EnvironByTikTok media was declared very feasible based on the results of the validation of material experts by obtaining a percentage of 96% and was also declared very feasible based on the results of the validation of media experts by obtaining a percentage of 88%. In addition, the assessment by teachers obtained a very practical category with an average assessment percentage of 100%, and the assessment from students obtained a very good category with an average percentage of 97.9%. The N-Gain score result of 0.675 indicates that the EnvironByTikTok media is effective with a moderate category to support the environmental literacy of high school students.